2017
DOI: 10.2192/ursu-d-15-00035.1
|View full text |Cite
|
Sign up to set email alerts
|

The late-denning activities of the American black bear in Utah

Abstract: EXECUTIVE SUMMARYDuring the early part of the 20 th Century, predators were subjected to high levels of take because of real or perceived threats to human health or safety and conflicts with agriculture/livestock. Many of our native predators have reestablished and are now very common in Oregon. The Oregon Department of Fish and Wildlife (ODFW or department) recognizes the high value of our native wildlife, including predators, and manages for a balance between sustainable populations and acceptable levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…The inverse relationship between maximum temperature and den exit in brown bears was also reported by Miller (1990), McLoughlin et al (2002, Manchi and Swenson (2005), and Delgado et al (2018), as well as for American black bears by Miller et al (2017) and Johnson et al (2017). In particular, Pigeon et al (2016) reported that for each increase of 4°C in spring temperature, den exit occurs 10 days earlier.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The inverse relationship between maximum temperature and den exit in brown bears was also reported by Miller (1990), McLoughlin et al (2002, Manchi and Swenson (2005), and Delgado et al (2018), as well as for American black bears by Miller et al (2017) and Johnson et al (2017). In particular, Pigeon et al (2016) reported that for each increase of 4°C in spring temperature, den exit occurs 10 days earlier.…”
Section: Discussionsupporting
confidence: 58%
“…These fluctuations may be caused by both interannual variations in climatic variables resulting from climate change and extreme climatic events and temperature anomalies, which have been predicted for southwestern Europe (Giorgi et al 2004, Castro et al 2005, Pendergrass et al 2017. These year-to-year changes in hibernation length have already been reported in American black bears (U. americanus; Miller et al 2017) and even in brown bears, where these changes depend on temperatures or precipitation during winter and spring (Miller 1990, Mcloughlin et al 2002, Friebe et al 2014, Evans et al 2016, Pigeon et al 2016, Johnson et al 2017, Delgado et al 2018. Therefore, identifying the triggers of den exit of FCOYs and its adjustment to climatic factors is of great importance and would allow for better predicting the effect of climate change on this vulnerable brown bear population.…”
mentioning
confidence: 76%
“…Warmer temperatures and shorter winters had reliably negative effects on hibernation emergence phenology, but studies of drier conditions were few (Table 1). A longer growing season, measured as last date of spring frost, had no effect on hibernation emergence in the one study where it was investigated (Miller et al 2017). Among the few positive effects on phenology were warmer fall temperatures delaying hibernation immergence in black bears Ursus americanus (Johnson et al 2018) and brown bears Ursus arctos (Evans et al 2016, Delgado et al 2018).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the increased climatic variability could make the weather patterns that govern the seasonality of animal life cycles to some extent more unpredictable for many organisms, including bears (Weiskopf et al, 2020). Actually, these interannual fluctuations in hibernation chronology due to climatic conditions have already been reported in both American black bears (Miller, Smith, Auger, Black, & Allphin, 2017) and brown bears (Delgado et al, 2018;Evans et al, 2016;Friebe et al, 2014;McLoughlin, Case, et al, 2002;. reported that for each 4°C increase in spring temperature brown bear den exit occurs 10 days earlier.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%